Zinc negative electrode containing protective film as well as preparation method and application of zinc negative electrode

The protective film is prepared by polyphenol-polyamine cross-linking technology, which solves the problems of high cost, complexity and poor effect of the existing zinc negative electrode protection method, and achieves high cycle stability and mechanical performance improvement of zinc negative electrode, which is suitable for large-scale production.

CN119673935AActive Publication Date: 2025-03-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311221202.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

The existing zinc negative electrode protection methods have problems such as high cost, complex methods, poor performance improvement effects, and inability to achieve large-scale preparation.

Method used

A protective film was prepared by polyphenol-polyamine cross-linking technology, and a stable protective layer was formed by immersing the zinc negative electrode in an aqueous solution of polyphenol and polyamine.

Benefits of technology

This method is simple and easy to implement, and can effectively improve the cyclic stability and mechanical properties of zinc negative electrodes, reduce dendrites' growth and corrosion, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673935A_ABST
    Figure CN119673935A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc negative electrode containing a protective film as well as a preparation method and application of the zinc negative electrode. The thickness of the protective film is 0.1 to 10 [mu] m; and the protective film is obtained by crosslinking polyphenol and polyamine. After polyphenol is oxidized, residual o-hydroxyl groups in a molecular structure can act on the surfaces of various substrates to generate strong non-covalent acting forces including electrostatic acting force, hydrogen bonds, pi-pi acting force, hydrophobic interaction force and the like, so that the coating has good adhesion. Polyphenols and polyamines are adopted for crosslinking, so that not only are high adhesion and integrity achieved, but also a film with good adhesion to a substrate can be formed through strong covalent interaction between polyphenols and polyamines, namely Michael addition and Schiff base reaction. The polyphenol-polyamine cross-linked structure not only enhances the mechanical properties of the film, but also introduces abundant functional groups such as hydroxyl, amido, carboxyl and the like to further optimize and regulate the deposition behavior of zinc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a zinc negative electrode containing a protective film and a preparation method and application thereof, belonging to the field of electrochemical materials. Background Art

[0002] With the growing demand for energy and the depletion of traditional fossil fuels and the resulting environmental pollution, clean and renewable energy sources (such as solar energy, wind energy, wind energy, and tidal energy) have greatly stimulated the research enthusiasm of researchers. Therefore, advanced energy storage systems are used to solve problems related to safe and sustainable energy storage. Among them, lithium-ion batteries dominate the application of secondary batteries and have achieved great success in the past 30 years. However, people are increasingly concerned about the challenges faced by lithium-ion batteries, such as limited lithium reserves, high cost, flammable and explosive electrolytes, and environmental problems, and there is an urgent need to find alternatives to lithium-ion batteries. Highly safe and eco-friendly aqueous zinc-ion batteries can effectively overcome the above challenges, and zinc metal reserves are abundant, cost-effective, and have a high theoretical capacity (820mAh g -1 ) and low redox potential (-0.76 V relative to standard hydrogen electrode), represent one of the most promising energy storage systems and are expected to become an alternative to lithium-ion batteries.

[0003] The Zn anode interface is unstable and causes some problems, such as hydrogen evolution reaction, corrosion, and the formation of by-products, resulting in low Coulombic efficiency and poor cycling stability. 2+ The uneven deposition of zinc ions during the stripping / electroplating process leads to the formation of zinc dendrites, which further deteriorates the utilization of zinc. In order to solve the above problems, researchers have developed various strategies to stabilize the zinc anode, such as electrolyte engineering, anode structure engineering, and surface coating. Artificially constructing an anode interface protective layer is an effective and simple strategy for achieving high performance and long cycle zinc-ion batteries.

[0004] Patent CN114792775A discloses a polymer-coated zinc anode and its preparation, wherein a polyvinylidene fluoride and hexafluoropropylene copolymer containing zinc salt or lithium salt is spin-coated on the zinc surface, but this method is limited to laboratory preparation. Considering that various current zinc anode protection strategies have one or more disadvantages such as high cost, complex methods, insignificant performance improvement effects, and inability to achieve large-scale preparation, it is necessary to develop new anode protection strategies to solve the above problems. Summary of the invention

[0005] In order to overcome the shortcomings of existing negative electrode protection methods, the present invention provides a method for preparing a polyphenol-polyamine cross-linked zinc negative electrode film, in which a series of low-cost, environmentally friendly polyphenol materials and polyamine materials with rich functional groups are cross-linked to prepare an artificial boundary protection layer to stabilize the zinc negative electrode. The method is simple to prepare and can be scaled up for production, providing a universal and effective method for improving problems such as dendrite growth, corrosion and side reactions.

[0006] According to one aspect of the present application, a zinc negative electrode containing a protective film is provided, wherein the thickness of the protective film is 0.1 to 10 μm;

[0007] The protective film is obtained by cross-linking polyphenol and polyamine.

[0008] The polyphenol is selected from at least one of dopamine, catechol, pyrogallol, tannic acid, tea polyphenols, gallic acid, and caffeic acid;

[0009] The polyamine is selected from at least one of polyethyleneimine, chitosan, diethylenetriamine, triethylenetetramine, triethylamine, m-phenylenediamine and p-phenylenediamine.

[0010] According to another aspect of the present application, a method for preparing the above-mentioned zinc negative electrode containing a protective film is provided, comprising the following steps:

[0011] The zinc negative electrode is immersed in an aqueous solution containing polyphenols and an aqueous solution containing polyamines in sequence, and then dried to obtain the zinc negative electrode containing the protective film.

[0012] In the aqueous solution containing polyphenols, the concentration of the polyphenols is 0.01 to 1 mol / L.

[0013] In the aqueous solution containing polyamines, the concentration of the polyphenols is 0.5-2 wt %.

[0014] The immersion time is 1 to 120 minutes.

[0015] The drying temperature is 40°C to 80°C;

[0016] The drying time is 4 hours to 12 hours.

[0017] Specifically, it is carried out in air at room temperature.

[0018] (1) Hydrophilic treatment of zinc foil: The zinc foil cut into 10×10 cm was ultrasonically cleaned with ethanol, immersed in HCl solution for a certain period of time to etch the surface, and then the zinc foil was taken out, cleaned with ethanol and dried.

[0019] The zinc foil has a thickness of 20 to 500 μm, preferably, the zinc foil has a thickness of 20 to 100 μm;

[0020] The zinc foil may be treated with 0.1 mol / L HCl for 10 min, 1 mol / L HCl for 5 min, 3 mol / L HCl for 30 s, 5 mol / L HCl for 10 s, preferably, 1 mol / L HCl for 5 min;

[0021] (2) The zinc foil was first immersed in the polyphenol solution for 5 minutes, and then most of the excess solution on the surface was removed. After a short drying, the zinc foil was immersed in the polyamine solution for 5 minutes, and most of the excess solution on the surface was removed. The zinc foil was then placed in an oven and dried at 60°C for 10 hours.

[0022] According to another aspect of the present application, an aqueous zinc ion battery is provided, comprising the above-mentioned zinc negative electrode containing a protective film.

[0023] The beneficial effects of this application include:

[0024] (1) The residual ortho-hydroxyl groups in the molecular structure of polyphenols after oxidation will act on the surfaces of various substrates, generating strong non-covalent forces including electrostatic forces, hydrogen bonds, π-π forces and hydrophobic interactions, which make the coating have good adhesion. The use of polyphenols and polyamines for cross-linking not only has high adhesion and integrity, but also can form a film with good adhesion to the substrate through strong covalent interactions between polyphenols and polyamines, namely Michael addition and Schiff base reaction.

[0025] (2) The cross-linked structure of polyphenol-polyamine not only enhances the mechanical properties of the film, but also introduces abundant functional groups such as hydroxyl, amine, and carboxyl to further optimize and regulate the zinc deposition behavior.

[0026] (3) The method of the invention is simple, and the functional molecules are cross-linked by covalent or non-covalent interactions without the need for multiple steps. The one-step preparation operation is simple and easy to perform, and is convenient for expanded production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM photograph of the zinc negative electrode of Comparative Example 1 of the present invention, with a scale of 1 μm.

[0028] Figure 2 This is a SEM photograph of the catechol-polyethyleneimine cross-linked film zinc negative electrode in Example 1 of the present invention, with a scale of 1 μm.

[0029] Figure 3 The zinc negative electrode symmetric battery prepared in Example 1 and Comparative Example 1 of the present invention is 0.5 mA cm -2 The current density of 1 mAh cm -2 Comparison of cycle performance under surface capacity.

[0030] Figure 4The zinc negative electrode symmetrical battery prepared in Example 2 of the present invention and Comparative Example 1 is 0.5 mA cm -2 The current density of 1 mAh cm -2 Comparison of cycle performance under surface capacity. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to examples, but the present application is not limited to the following examples.

[0032] Comparative Example 1

[0033] A 100 μm zinc foil was cut into 10×10 cm and treated with 1 mol / L HCl for 5 min. The zinc foil was then removed, the surface was cleaned with ethanol and dried.

[0034] Figure 1 This is a SEM photograph of the zinc negative electrode of Comparative Example 1 of the present invention, with a scale of 1 μm.

[0035] Example 1

[0036] (1) A 100 μm zinc foil was cut into 10 × 10 cm pieces and treated with 1 mol / L HCl for 5 min. The zinc foil was then removed and the surface was cleaned with ethanol and dried.

[0037] (2) Prepare a fresh 0.05 mol / L aqueous solution of catechol and a fresh 1.5 wt. % aqueous solution of polyethyleneimine, and dissolve the two solutions by ultrasonication for 10 min.

[0038] (3) The hydrophilized zinc foil was placed in a freshly prepared aqueous solution of catechol, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried at 60°C. Then, the zinc foil was placed in a freshly prepared aqueous solution of polyethyleneimine, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried.

[0039] Figure 2 This is a SEM photograph of the catechol-polyethyleneimine cross-linked film zinc negative electrode in Example 1 of the present invention, with a scale of 1 μm.

[0040] Example 2

[0041] (1) A 100 μm zinc foil was cut into a certain size and treated with 1 mol / L HCl for 5 min. The zinc foil was then removed, the surface was cleaned with ethanol, and then dried.

[0042] (2) Prepare a fresh 0.05 mol / L catechol aqueous solution and a 1.5 wt. % chitosan aqueous solution, and dissolve the two solutions by ultrasonication for 10 min.

[0043] (3) The hydrophilized zinc foil was placed in a freshly prepared aqueous solution of catechol, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried at 60°C. The zinc foil was then placed in a freshly prepared aqueous solution of chitosan, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried.

[0044] Example 3

[0045] (1) A 100 μm zinc foil was cut into a certain size and treated with 0.1 mol / L HCl for 10 min. The zinc foil was then removed, the surface was cleaned with ethanol, and dried at 60 °C for 1 h.

[0046] (2) Prepare a fresh 0.1 mol / L tannic acid aqueous solution and a 1 wt % polyethyleneimine aqueous solution, and dissolve the two solutions by ultrasonication for 10 min.

[0047] (3) The hydrophilized zinc foil was placed in a freshly prepared tannic acid aqueous solution, and after standing at room temperature for 5 minutes, the zinc foil was taken out, and the excess solution on the surface was removed and then dried at 60°C. The zinc foil was then placed in a freshly prepared polyethyleneimine aqueous solution, and after standing at room temperature for 5 minutes, the zinc foil was taken out, and the excess solution on the surface was removed and then dried.

[0048] Example 4

[0049] (1) Cut 100 μm zinc foil into certain sizes, treat it with 10 mol / L HCl for 10 s, then remove the zinc foil and rinse it with ethanol.

[0050] Clean the surface and dry it.

[0051] (2) Prepare a fresh 0.1 mol / L aqueous solution of molar acid and a 1 wt. % aqueous solution of polyethyleneimine, and dissolve the two solutions by ultrasonication for 10 min.

[0052] (3) The hydrophilized zinc foil was placed in a freshly prepared aqueous solution of ethyl imine, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried at 60°C. The zinc foil was then placed in a freshly prepared aqueous solution of polyethyleneimine, and after standing at room temperature for 5 minutes, the zinc foil was taken out, the excess solution on the surface was removed, and then the zinc foil was dried.

[0053] Example 5

[0054] (1) A 100 μm zinc foil was cut into a certain size and treated with 1 mol / L HCl for 5 min. The zinc foil was then removed, the surface was cleaned with ethanol, and dried at 60 °C for 1 h.

[0055] (2) Prepare a fresh 0.01 mol / L dopamine aqueous solution and a 1 wt % polyethyleneimine aqueous solution, and dissolve the two solutions by ultrasonication for 10 min.

[0056] (3) The hydrophilized zinc foil was placed in a freshly prepared dopamine aqueous solution, allowed to stand at room temperature for 5 min, then taken out, the excess solution on the surface was removed, and then dried at 60°C. The zinc foil was then placed in a freshly prepared polyethyleneimine aqueous solution, allowed to stand at room temperature for 5 min, then taken out, the excess solution on the surface was removed, and then dried.

[0057] Example 6

[0058] (1) The zinc negative electrodes prepared in Examples 1 to 5 and Comparative Example 1 were cut into 15 mm diameter electrode sheets to assemble symmetrical batteries, wherein the positive and negative electrodes were zinc sheets of untreated zinc and polyphenol-polyamine protective films, the separator was glass fiber, and the electrolyte was 2 mol / L Zn(CH 3 SO 3 ) 2 The zinc negative electrode is placed in the positive electrode shell, followed by the positive electrode sheet and the diaphragm, and the electrolyte is dripped until the diaphragm is completely wetted. Then, the negative electrode sheet, stainless steel gasket, spring and negative electrode shell are placed in turn, and then placed in a static press for static pressure sealing, thereby preparing an aqueous zinc ion symmetrical battery.

[0059] (2) Symmetrical battery performance test: The assembled symmetrical battery is clamped in the battery channel of the Xinwei test system for testing at 0.5 mA cm -2 The current density of 1 mAh cm -2 Constant current charge and discharge test was carried out at the surface capacity.

[0060] Figure 3 The zinc negative electrode symmetric battery prepared in Example 1 and Comparative Example 1 of the present invention is 0.5 mA cm -2 The current density of 1 mAh cm -2 Comparison of cycle performance under surface capacity.

[0061] Figure 4 The zinc negative electrode symmetrical battery prepared in Example 2 of the present invention and Comparative Example 1 is 0.5 mA cm -2 The current density of 1 mAh cm -2 Comparison of cycle performance under surface capacity.

[0062] As can be seen from the figure, the catechol and polyethyleneimine cross-linked thin film zinc negative electrode has better cycle life and cycle stability than the bare zinc negative electrode.

[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A zinc negative electrode containing a protective film, characterized in that: The thickness of the protective film is 0.1 to 10 μm; The protective film is obtained by cross-linking polyphenol and polyamine.

2. The zinc negative electrode containing a protective film according to claim 1, characterized in that: The polyphenol is selected from at least one of dopamine, catechol, pyrogallol, tannic acid, tea polyphenols, gallic acid, and caffeic acid; The polyamine is selected from at least one of polyethyleneimine, chitosan, diethylenetriamine, triethylenetetramine, triethylamine, m-phenylenediamine and p-phenylenediamine.

3. A method for preparing a zinc negative electrode containing a protective film according to any one of claims 1 or 2, characterized in that: The following steps are involved: The zinc negative electrode is immersed in an aqueous solution containing polyphenols and an aqueous solution containing polyamines in sequence, and then dried to obtain the zinc negative electrode containing the protective film.

4. The preparation method according to claim 3, characterized in that: In the aqueous solution containing polyphenols, the concentration of the polyphenols is 0.01 to 1 mol / L.

5. The preparation method according to claim 3, characterized in that: In the aqueous solution containing polyamines, the concentration of the polyphenols is 0.5-2 wt %.

6. The preparation method according to claim 3, characterized in that: The immersion time is 1 to 120 minutes.

7. The preparation method according to claim 3, characterized in that: The drying temperature is 40°C to 80°C; The drying time is 4 hours to 12 hours.

8. An aqueous zinc ion battery, characterized in that: A zinc negative electrode containing a protective film as described in any one of claims 1 or 2.

Citation Information

Patent Citations

  • Lithium battery negative current collector and preparation method thereof

    CN110518253A

  • Preparation method and application method of lithium battery negative electrode current collector surface modifier for preventing lithium dendrite deposition

    CN111446452A

  • Zinc negative electrode and preparation method and application thereof

    CN114597407A

  • Preparation method of macromolecular polyphenol zinc complex as zinc negative electrode protection layer

    CN114628681A

  • Negative electrode material, preparation method, secondary battery and electric equipment

    CN116632172A